Advances in nailfold capillaroscopic analysis in systemic sclerosis. Issue 2 (June 2018) - Ruaro, Barbara; Sulli, Alberto; Smith, Vanessa; Pizzorni, Carmen; Paolino, Sabrina; Alessandri, Elisa; Trombetta, Amelia Chiara; Cutolo, Maurizio
Systemic sclerosis is an autoimmune connective tissue disease characterized by early and persistent microvascular impairment which leads to functional and organic manifestations, with progressive fibrosis of the skin and internal organs. Morphological and functional assessment of the peripheral microvasculature is a must, not only for diagnosis but also for the prognosis and therapeutical follow-up of systemic sclerosis patients, as reported in recent studies. Nailfold videocapillaroscopy is the validated technique for the study of scleroderma microangiopathy as it is able to detect peripheral microvascular morphology and both classify and score the capillary abnormalities into different microangiopathy patterns ('Early', 'Active' and 'Late'). Indeed, the possibility to early diagnose and follow the microvascular changes and the safety of the technique have made nailfold videocapillaroscopy a mandatory tool for patient evaluation and included its assessment in the new systemic sclerosis classification criteria. Important links between nailfold videocapillaroscopy patterns and systemic sclerosis clinical manifestations have been described.